Critical Examination of Healthcare Access Strategies and Their Implications on Public Health - Alhamadah, Feda Adil; Al Hakeem, Hawra Abdullah; Al Lashet, Afrah Jafer Abbas; Al Lashet, Zainab Jafer Abbas; Al Mohanna, Fatimah Jaafer Ahmmed; Alrashed, Sadiq Habeeb Ali; Aljanabi, Hassan Ali; Tawhari, Adel Omar shui; Al Muraibt, Zainab Mahdi; Muaini, Eman Mohamed Hassan (Journal of Ecohumanism, 2024)
Healthcare accessibility is one of the main determinants of health in the population and the world. The three A’s, access, cost, and availability of health facilities, play a significant role in how quality health care is being delivered and, in the effort, to prevent diseases and improve the health standards of the communities. Analyzing healthcare access models, this paper discusses best practices as well as problems that have been observed in different world regions. Major factors are assessed, including UHC, selective health policies, PPL, and the implementation of technologies for describing and increasing access to health care services. The research also focuses on a particular aspect of healthcare availability: the number of accessible healthcare facilities available to people and the extent to which they can address the population’s health needs in terms of existing disparities, economic burden, and response to emerging public health issues. This paper analyzes global case studies that reveal emerging challenges and suggest solutions to strengthen healthcare access for diverse populations.